Mechanisms underlying Actinobacillus pleuropneumoniae exotoxin ApxI induced expression of IL-1β, IL-8 and TNF-α in porcine alveolar macrophages - Chen, Zeng-Weng; Chien, Maw-Sheng; Chang, Nai-Yun; Chen, Ter-Hsin; Wu, Chi-Ming; Huang, Chienjin; Lee, Wei-Cheng; Hsuan, Shih-Ling (Veterinary research (Paris), 2011)
Actinobacillus pleuropneumoniae ( A. pleuropneumoniae ) causes fibrino-hemorrhagic necrotizing pleuropneumonia in pigs. Production of proinflammatory mediators in the lungs is an important feature of A. pleuropneumoniae infection. However, bacterial components other than lipopolysaccharide involved in this process remain unidentified. The goals of this study were to determine the role of A. pleuropneumoniae exotoxin ApxI in cytokine induction and to delineate the underlying mechanisms. Using real-time quantitative PCR analysis, we found native ApxI stimulated porcine alveolar macrophages (PAMs) to transcribe mRNAs of IL-1β, IL-8 and TNF-α in a concentration- and time-dependent manner. Heat-inactivation or pre-incubation of ApxI with a neutralizing antiserum attenuated ApxI bioactivity to induce cytokine gene expression. The secretion of IL-1β, IL-8 and TNF-α protein from PAMs stimulated with ApxI was also confirmed by quantitative ELISA. In delineating the underlying signaling pathways contributing to cytokine expression, we observed mitogen-activated protein kinases (MAPKs) p38 and cJun NH2-terminal kinase (JNK) were activated upon ApxI stimulation. Administration of an inhibitor specific to p38 or JNK resulted in varying degrees of attenuation on ApxI-induced cytokine expression, suggesting the differential regulatory roles of p38 and JNK in IL-1β, IL-8 and TNF-α production. Further, pre-incubation of PAMs with a CD18-blocking antibody prior to ApxI stimulation significantly reduced the activation of p38 and JNK, and subsequent expression of IL-1β, IL-8 or TNF-α gene, indicating a pivotal role of β2 integrins in the ApxI-mediated effect. Collectively, this study demonstrated ApxI induces gene expression of IL-1β, IL-8 and TNF-α in PAMs that involves β2 integrins and downstream MAPKs.